Aplikasi Komposisi Dosis Pemupukan NPK Dalam Pupuk Urea, TSP Dan KCl Berdasarkan Metode Diagnosis and Recommendation Integrated System (DRIS) Untuk Tanaman Cabai Besar (Capsicum annum L.) Pada Tanah Mineral Masam Gunung Kupang Kecamatan Cempaka Banjarbaru - Maulana, Irfan; Mahbub, Muhammad; Syaifuddin, Syaifuddin (Agroekotek View, 2024)
Big chili is a type of national superior vegetable commodity whose productivity will always be increased. Balanced fertilization is a solution to increase the production of big chilies, in analyzing crop yields the recommendation for balanced fertilization in an integrated manner is the dris method. This research to determine the effect of balanced fertilization of NPK in urea, TSP and Kcl based on the DRIS method on  number of leaves,  number of branches, plant height, flowering time, wet weight and dry weight. This research was carried out in an Agroecotechnology's greenhouse from July to September 2021. The research method used onefactor RAL with 6 treatments; D0 (control), D1 (0.90 g Urea + 0.09 g TSP + 1.94 g KCl), D2 (1.35 g Urea + 0.09 g TSP + 2.08 g KCl), D3 (1 .80 g Urea + 0.09 g TSP + 2.31 g KCl), D4 (2.70 g Urea + 0.09 g TSP + 2.78 g KCl), D5 (3.15 g Urea + 0.09 g TSP + 2.79 g KCl) and repeated four times to obtain 24 experimental units. The results of this research showed that D1 had a significant effect on plant height.